Cardiac damage in autoimmune diseases: Target organ involvement that cannot be ignored - Pan, Shu-Yue; Tian, Hui-Min; Zhu, Yong; Gu, Wei-Jie; Zou, Hao; Wu, Xu-Qiang; Cheng, Rui-Juan; Yang, Zhi (Frontiers in Immunology, 2022)
Autoimmune diseases are diseases that cause damage to the body's own tissues as a result of immune dysfunction and often involve multiple organs and systems. The heart is one of the common target organs of autoimmune diseases, which can involve the whole structure of the heart, including microcirculatory disorders, arrhythmias, pericardial damage, myocarditis, myocardial fibrosis, and impaired valve function. However, the early clinical manifestations of autoimmune heart damage are often overlooked because they are insidious or have no typical features, and when symptoms are obvious, the damage is often severe and irreversible and often life-threatening. Therefore, early detection and treatment of heart damage in autoimmune diseases is particularly important. In this article, we review the clinical features and mechanisms of cardiac damage in common rheumatic diseases.